PENGARUH KETERLAMBATAN WAJIB PAJAK, PENGETAHUAN PAJAK DAN RAZIA LAPANGAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN MALAKA NUSA TENGGARA TIMUR: PENGARUH KETERLAMBATAN WAJIB PAJAK, PENGETAHUAN PAJAK DAN RAZIA LAPANGAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN MALAKA NUSA TENGGARA TIMUR - Luruk Seran, Stefania; Dewi Astuti, Tutut (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the effect of taxpayer delays, tax knowledge, and field raids on motor vehicle taxpayer compliance in Malaka Regency, East Nusa Tenggara. The sample size is determined through the Slovin formula which produces a sample size of 100 samples. The data source consists of primary data. The data collection method is carried out by distributing questionnaires. The data analysis method used is multiple linear regression testing. Data analysis using SPSS. The results of this study indicate that (1. Tax delays affect motor vehicle taxpayer compliance at the Samsat Office of Malaka Regency, East Nusa Tenggara can be accepted) (2. Tax knowledge affects motor vehicle taxpayer compliance at the Samsat Office of Malaka Regency, East Nusa Tenggara is rejected) (3. Field raids affect motor vehicle taxpayer compliance at the Samsat Office of Malaka Regency, East Nusa Tenggara can be accepted)